Enhancing Critical Thinking through AI and Simulation - Zulkifli Zulkifli; Akhsanul Inam; Dyah Worowirastri Ekowati (Yayasan Keluarga Guru Mandiri, 2025)
This study investigates the effectiveness of Artificial Intelligence (AI) and simulation-based learning in improving students’ critical thinking skills in Information and Communication Technology (ICT) instruction at MTs Qur’aniyah Narmada, West Lombok. The research used a quasi-experimental design with nonequivalent control groups, involving 44 seventh-grade students divided into two experimental classes. One class was taught using AI-integrated applications, while the other employed simulation-based methods. Data were collected through critical thinking tests and student response questionnaires, then analyzed using descriptive statistics and independent t-tests. The results showed that the AI class achieved a higher average score (81.14) than the simulation class (73.41), with a statistically significant difference (t = 2.267, p 0.05). These findings suggest that AI offers immediate feedback, adaptive learning, and deeper cognitive engagement, making it more effective than traditional simulation approaches in promoting critical thinking. The study concludes that integrating AI into ICT learning can significantly enhance digital literacy and higher-order thinking skills. This research contributes to the scientific discourse by offering a practical instructional model for madrasahs, especially in rural Indonesian settings. It supports the development of 21st-century competencies among students through innovative, technology-enhanced learning environments.